2023
DOI: 10.3390/nu15214666
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions to Prevent Type 2 Diabetes in Women with a History of Gestational Diabetes: A Systematic Review and Meta-Analysis through the Lens of Health Equity

Gebresilasea Gendisha Ukke,
Jacqueline A. Boyle,
Ahmed Reja
et al.

Abstract: Background: Type 2 diabetes mellites is one of the health problems disproportionally affecting people with low socioeconomic statuses. Gestational diabetes mellites increases the risk of type 2 diabetes by up to ten-fold for women. Lifestyle interventions prevent type 2 diabetes in women with prior gestational diabetes. However, it is unknown if similar effectiveness can be expected for all population subgroups. Objective: This study aims to assess the prevention of type 2 diabetes in women with prior gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(111 reference statements)
0
0
0
Order By: Relevance
“…Risk factors for T2D among those with a history of GDM included greater pre-pregnancy Body Mass Index (BMI), excessive weight gain, unhealthy dietary patterns, physical inactivity, and a short period of lactation [ 13 ]. Post-natal risk, such as missing medical assistance in the continuum of GDM care after delivery, could be another risk for progression to T2D among Asian mothers with a history of GDM [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for T2D among those with a history of GDM included greater pre-pregnancy Body Mass Index (BMI), excessive weight gain, unhealthy dietary patterns, physical inactivity, and a short period of lactation [ 13 ]. Post-natal risk, such as missing medical assistance in the continuum of GDM care after delivery, could be another risk for progression to T2D among Asian mothers with a history of GDM [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most preventative studies are undertaken in Western countries [ 21 ], and it is challenging to directly apply these strategies in Asian countries due to differences in demographics, socioeconomics, ethnicity, and cultural factors [ 7 ]. A recent systematic review study concluded that in most of the studies, the evidence-based intervention might not be culturally appropriate for the prevention of T2D in women with a history of GDM [ 13 ].…”
Section: Introductionmentioning
confidence: 99%